Bone china and its production process
By integrating pre-fired andalusite and chrysotile fibers into the bone china formulation and optimizing the glazing process, the thermal shock resistance and mechanical strength of bone china are significantly improved.
Patent Information
- Application Number
- CN202411295466.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-18
AI Technical Summary
Traditional bone china exhibits poor thermal shock resistance, which hinders its quality improvement.
Incorporating andalusite and chrysotile fibers into the bone china composition, pre-firing them, and utilizing their mullite reaction under high-temperature firing to enhance thermal shock resistance, combined with a specific glazing process to improve mechanical strength.
The resulting bone china demonstrates enhanced thermal shock resistance and bending strength, outperforming traditional methods.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic formed products, and in particular relates to bone china and a production process thereof. Background Art
[0002] Bone china is also called bone ash china. The basic process is to use animal bone powder, clay, feldspar and quartz as the basic raw materials, and it is a kind of porcelain made by high-temperature bisque firing and low-temperature glaze firing. In daily-use ceramics, bone china is widely used. The performance of bone china is closely related to its physical composition. The physical composition of traditional bone china is mainly tricalcium phosphate, calcium feldspar and a certain amount of phosphate glass phase. It has the advantages of white porcelain, high light transmittance and soft luster, but it also has the disadvantage of poor thermal shock resistance. Improving the thermal shock resistance of bone china is a key technical issue in improving the quality of bone china. Therefore, the research and development of a bone china with good thermal shock resistance is not only of great significance to the development of bone china, but also of great significance to the field of ceramic molded products.
[0003] Related technologies are disclosed in the prior art:
[0004] The Chinese patent with publication number CN111675534B discloses a heat-resistant porcelain with high thermal shock resistance, which uses natural mineral raw materials and industrial chemical raw materials, and the weight percentage of the materials is as follows: lithium porcelain stone 25-30%, kaolin 20-30%, magnesium carbonate 10-15%, bauxite 15-20%, ammonium molybdate 2-5%, spodumene 5-10%, potassium feldspar 5-10%, and the heat-resistant porcelain product is obtained through the following steps: batching, ball milling, adding 10-15% pre-burned material, mixing, sieving, filtering, squeezing mud, kneading mud, aging, molding, drying, glazing, secondary drying, and firing. It is easy to implement, has a high yield rate, good product quality, and can greatly improve the thermal stability and mechanical strength of the product.
[0005] The Chinese patent with publication number CN106242504B discloses a reinforced bone daily porcelain and its preparation method. The reinforced bone daily porcelain is prepared by using the following raw materials in the following mass fractions: according to the mass fractions, it is prepared by using the following raw materials: additive ZL 1-3 parts, bone carbon 40-45 parts, quartz 10-12 parts, feldspar 10-12 parts, kaolin 24-28 parts, water 48-52 parts, crystal form improver 1-3 parts, mineralizer 1-2 parts, phosphosilicate targeted flux 1-3 parts. The invention scientifically introduces the phosphosilicate targeted flux, thereby significantly reducing the introduction of potassium and sodium minerals in the raw materials, and at the same time well controls the sintering temperature and expansion coefficient of the blank. At the same time, in the composition of bone porcelain mud, the additive ZL, crystal form improver and mineralizer components are introduced to ensure the uniform growth and development of crystals in the vitrification porcelain stage, and the phosphosilicate glass phase network is further complete, and finally the mechanical strength of the bone porcelain is enhanced and its thermal vibration resistance is improved. The product of the invention has high mechanical strength, smooth glaze surface and is easy to clean, the amount of lead and cadmium dissolution is significantly reduced, and it has good thermal vibration resistance. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a bone china, characterized in that the bone china comprises the following raw materials in parts by weight: 40-55 parts of bone meal, 5-10 parts of andalusite, 5-10 parts of chrysotile, 10-16 parts of feldspar, 6-12 parts of quartz, 8-15 parts of clay, and 2-5 parts of glaze.
[0007] Furthermore, the mass ratio of andalusite to chrysotile fibers is 2:1.
[0008] Furthermore, the glaze is made of the following raw materials: 15-25 parts of feldspar, 10-20 parts of quartz, 20-30 parts of frit, 5-8 parts of kaolin, and 3-5 parts of zinc oxide.
[0009] The present invention also provides a production process of bone china as described herein, which comprises the following steps:
[0010] S1, mixing andalusite and chrysotile in required weight portions in a ball mill, and then pre-calcining;
[0011] S2, adding bone meal, feldspar, quartz, clay in required weight proportions and the pre-sintered product obtained in step S1 and the same weight of water into a ball mill for ball milling, followed by sieving, aging and molding to obtain a green body;
[0012] S3, bisque-firing, glazing, glaze-firing and then naturally cooling the body to obtain the bone china.
[0013] Furthermore, the ball milling time in step S1 is 1-2 hours.
[0014] Furthermore, the pre-sintering in step S1 is performed at 1500-1600° C. for 1-2 hours.
[0015] Furthermore, the ball milling time in step S2 is 3-6 hours.
[0016] Furthermore, the biscuit calcination in step S3 is carried out at 1250-1300° C. for 3-6 hours.
[0017] Furthermore, the glaze used for glazing in step S3 is prepared as follows: the required weight portions of feldspar, quartz, frit, kaolin and zinc oxide are respectively crushed to a fineness of 200 mesh, mixed to obtain a glaze mixture, and wet-milled in a ball mill at a ratio of glaze mixture: ball: water = 1: (1.5-2): 0.7, and the obtained glaze slurry is sequentially passed through a 180-mesh sieve, a 250-mesh sieve, and a 300-mesh sieve, and the sieved material is selected by a high-intensity wet magnetic separator for more than five times to remove iron substances, thereby obtaining a glaze.
[0018] Furthermore, the specific gravity of the glaze is 1.50-1.55, the glaze spraying pressure is 2-3kg / cm3, and the thickness of the glaze layer is 0.2-0.25mm.
[0019] Furthermore, the glaze firing in step S3 is carried out at 1100-1200° C. for 1-3 hours.
[0020] Beneficial effects of the present invention:
[0021] Compared with the prior art, the present invention adds pre-fired andalusite and chrysotile to the basic raw materials of traditional bone meal, clay, feldspar and quartz, utilizes the mullite reaction of andalusite under high-temperature firing, and can use chrysotile as a template to grow mullite fiber, which is then added to the bone china formula. It is found that the thermal shock resistance of the bone china product can be improved, and the bending strength is also improved. DETAILED DESCRIPTION
[0022] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0023] Example 1
[0024] A bone china comprises the following raw materials in parts by weight: 40 parts of bone meal, 6 parts of andalusite, 3 parts of chrysotile, 16 parts of feldspar, 12 parts of quartz, 15 parts of clay, and 4 parts of glaze. The production process thereof comprises the following steps:
[0025] S1. Mill and mix the required weight proportions of andalusite and chrysotile in a ball mill for 1 hour, and then pre-calcine at 1600° C. for 1 hour;
[0026] S2, adding bone meal, feldspar, quartz, clay in the required weight proportions and the pre-sintered product obtained in step S1 and the same weight of water into a ball mill, ball milling for 3 hours, and then passing through a 100-mesh sieve to obtain a sieved material, leaving the sieved material to stand and age for 3 days to obtain a blank, and injecting the blank into a mold to form a green body;
[0027] S31, placing the green body into a kiln and firing it at 1300°C for 3 hours, during which time high-temperature insulation is appropriately performed;
[0028] S32, preparing glaze: crushing 16 parts of feldspar, 14 parts of quartz, 25 parts of frit, 6 parts of kaolin and 4 parts of zinc oxide to a fineness of 200 meshes by weight, mixing to obtain a glaze mixture, wet-grinding in a ball mill at a ratio of glaze mixture: ball: water = 1:2:0.7, passing the obtained glaze slurry through a 180-mesh sieve, a 250-mesh sieve and a 300-mesh sieve in sequence, and selecting the sieved material five times with a high-intensity wet magnetic separator to remove iron substances, thereby obtaining a glaze;
[0029] S33, glazing the obtained bisque-fired body by glaze spraying, with a glaze slurry specific gravity of 1.50, a glaze spraying pressure of 3 kg / cm3, and a glaze layer thickness of 0.2 mm;
[0030] S34, firing the glazed product at 1150°C for 2 hours and naturally cooling it to room temperature to obtain bone china.
[0031] Example 2
[0032] A bone china comprises the following raw materials in parts by weight: 48 parts of bone meal, 8 parts of andalusite, 4 parts of chrysotile, 13 parts of feldspar, 10 parts of quartz, 10 parts of clay, and 4 parts of glaze. The production process thereof comprises the following steps:
[0033] S1. Mix andalusite and chrysotile in the required weight proportions in a ball mill for 2 h, and then pre-calcine at 1600° C. for 2 h;
[0034] S2, adding bone meal, feldspar, quartz, clay in the required weight proportions and the pre-sintered product obtained in step S1 and the same weight of water into a ball mill, ball milling for 3 hours, and then passing through a 100-mesh sieve to obtain a sieved material, leaving the sieved material to stand and age for 3 days to obtain a blank, and injecting the blank into a mold to form a green body;
[0035] S31, placing the green body into a kiln and firing it at 1300°C for 5 hours, during which time high-temperature insulation is appropriately performed;
[0036] S32, preparing glaze: crushing 16 parts of feldspar, 14 parts of quartz, 25 parts of frit, 6 parts of kaolin and 4 parts of zinc oxide to a fineness of 200 meshes by weight, mixing to obtain a glaze mixture, wet-grinding in a ball mill at a ratio of glaze mixture: ball: water = 1:2:0.7, passing the obtained glaze slurry through a 180-mesh sieve, a 250-mesh sieve and a 300-mesh sieve in sequence, and selecting the sieved material five times with a high-intensity wet magnetic separator to remove iron substances, thereby obtaining a glaze;
[0037] S33, glazing the obtained bisque-fired body by glaze spraying, with a glaze slurry specific gravity of 1.50, a glaze spraying pressure of 3 kg / cm3, and a glaze layer thickness of 0.2 mm;
[0038] S34, firing the glazed product at 1200°C for 1 hour and naturally cooling it to room temperature to obtain bone china.
[0039] Example 3
[0040] A bone china comprises the following raw materials in parts by weight: 55 parts of bone meal, 10 parts of andalusite, 5 parts of chrysotile, 10 parts of feldspar, 6 parts of quartz, 8 parts of clay, and 4 parts of glaze. The production process thereof comprises the following steps:
[0041] S1. Mill and mix the required weight proportions of andalusite and chrysotile in a ball mill for 1 hour, and then pre-calcine at 1500° C. for 2 hours;
[0042] S2, adding bone meal, feldspar, quartz, clay in required weight proportions and the pre-sintered product obtained in step S1 and the same weight of water into a ball mill, ball milling for 6 hours, and then passing through a 100-mesh sieve to obtain a sieved material, leaving the sieved material to stand and age for 5 days to obtain a blank, and injecting the blank into a mold to form a green body;
[0043] S31, placing the green body into a kiln and firing it at 1250°C for 6 hours, during which time high-temperature insulation is appropriately performed;
[0044] S32, preparing glaze: crushing 16 parts of feldspar, 14 parts of quartz, 25 parts of frit, 6 parts of kaolin and 4 parts of zinc oxide to a fineness of 200 meshes by weight, mixing to obtain a glaze mixture, wet-grinding in a ball mill at a ratio of glaze mixture: ball: water = 1:2:0.7, passing the obtained glaze slurry through a 180-mesh sieve, a 250-mesh sieve and a 300-mesh sieve in sequence, and selecting the sieved material five times with a high-intensity wet magnetic separator to remove iron substances, thereby obtaining a glaze;
[0045] S33, glazing the obtained bisque-fired body by glaze spraying, with a glaze slurry specific gravity of 1.50, a glaze spraying pressure of 3 kg / cm3, and a glaze layer thickness of 0.2 mm;
[0046] S34, firing the glazed product at 1100°C for 3 hours and naturally cooling it to room temperature to obtain bone china.
[0047] Comparative Example 1
[0048] A bone china and a production process thereof, which differs from Example 1 in that andalusite and chrysotile are not added.
[0049] Comparative Example 2
[0050] A bone china and a production process thereof, which differs from Example 1 in that the added andalusite and chrysotile are not pre-fired and are directly ball-milled with other raw materials.
[0051] Comparative Example 3
[0052] A bone china and a production process thereof, which differs from Example 1 in that only the added andalusite is pre-fired, while the chrysotile is not pre-fired and is directly ball-milled with other raw materials.
[0053] Comparative Example 4
[0054] A bone china and a production process thereof, which differs from Example 1 in that andalusite and chrysotile are pre-sintered at 1400°C.
[0055] Comparative Example 5
[0056] A bone china and a production process thereof, which differs from Example 1 in that the pre-firing of andalusite and chrysotile is carried out at 1300°C.
[0057] Comparative Example 6
[0058] A bone china and a production process thereof, which differs from Example 1 in that the mass ratio of andalusite to chrysotile is 1:1, that is, the added amount is 4.5 parts by weight.
[0059] Comparative Example 7
[0060] A bone china and a production process thereof, which differs from Example 1 in that the mass ratio of andalusite to chrysotile is 1:2, that is, the added amounts are 3 parts and 6 parts respectively.
[0061] The bone china obtained in the above examples and comparative examples was tested, and the specific tests were as follows:
[0062] 1. Bending strength: The three-point bending method is used and the WDS-5 electronic universal testing machine is used for measurement;
[0063] 2. Thermal shock resistance: According to GB / T13522 "Bone China" standard, the bone china obtained in the above examples and comparative examples was tested to see whether cracks were generated after a heat exchange from 220°C to 20°C.
[0064] The results are shown in Table 1.
[0065] Bending strength / MPa 220℃ to 20℃ heat exchange once to see if cracks occur Example 1 121.35 none Example 2 128.68 none Example 3 124.22 none Comparative Example 1 97.55 have Comparative Example 2 103.45 have Comparative Example 3 111.36 have Comparative Example 4 117.51 none Comparative Example 5 109.43 have Comparative Example 6 118.32 none Comparative Example 7 115.47 none
[0066] From the results in Table 1, it can be seen that the bone china of Examples 1-3 has a high bending strength and good thermal shock resistance. However, the bone china prepared without adding andalusite and chrysotile, without pre-firing the added andalusite and chrysotile, and without pre-firing the added andalusite and chrysotile not only has a significantly reduced bending strength, but also has poor thermal shock resistance. In addition, Comparative Examples 4-7 also confirm that the pre-firing temperature of andalusite and chrysotile and the addition ratio of the two have a great influence on the improvement of the bending resistance, which further affects the thermal shock resistance of the bone china.
[0067] It should be noted that the preferred embodiments of the present invention are given in the specification of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.
Claims
1. A production process for bone china, wherein the bone china is composed of the following raw materials in parts by weight: 40-55 parts of bone meal, 6-10 parts of andalusite, 3-5 parts of chrysotile, 10-16 parts of feldspar, 6-12 parts of quartz, 8-15 parts of clay, 2-5 parts of glaze, characterized in that the production process comprises the following steps: S1. Mix andalusite and chrysotile in the required weight portions in a ball mill, and then pre-calcine them at 1500-1600° C. for 1-2 hours; S2, adding bone meal, feldspar, quartz, clay in required weight proportions and the pre-sintered product obtained in step S1 and the same weight of water into a ball mill for ball milling, followed by sieving, aging and molding to obtain a green body; S3, bisque-firing, glazing, glaze-firing and then naturally cooling the body to obtain the bone china.
2. The production process according to claim 1, characterized in that: The mass ratio of andalusite to chrysotile fibers is 2:
1.
3. The production process according to claim 1, characterized in that: The glaze is made of the following raw materials: 15-25 parts of feldspar, 10-20 parts of quartz, 20-30 parts of frit, 5-8 parts of kaolin and 3-5 parts of zinc oxide.
4. The production process according to claim 1, characterized in that: The ball milling time in step S1 is 1-2 hours.
5. The production process according to claim 1, characterized in that: The ball milling time in step S2 is 3-6 hours.
6. The production process according to claim 1, characterized in that: The biscuit calcination in step S3 is carried out at 1250-1300° C. for 3-6 hours.
7. The production process according to claim 1, characterized in that: The glaze used in the glazing of step S3 is prepared as follows: the required weight portions of feldspar, quartz, frit, kaolin and zinc oxide are respectively crushed to a fineness of 200 mesh, mixed to obtain a glaze mixture, and wet-milled in a ball mill according to the ratio of glaze mixture: ball: water = 1: (1.5-2): 0.7, and the obtained glaze slurry is sequentially passed through a 180 mesh sieve, a 250 mesh sieve, and a 300 mesh sieve, and the sieved material is selected by a high-intensity wet magnetic separator for more than five times to remove iron substances, thereby obtaining a glaze. The specific gravity of the glaze is 1.50-1.55, and the glaze spraying pressure is 2-3kg / cm 3 The thickness of the glaze layer is 0.2-0.25mm.
8. The production process according to claim 1, characterized in that: The glaze firing in step S3 is carried out at 1100-1200° C. for 1-3 hours.